Application of ISAK 35 concerning Financial Statements of Non-profit Organizations at the HKBP Bolon Pangururan Church - Sofia Imelda Simbolon; Sahala Purba (Asian Journal of Applied Business and Management, 2022)
The importance of preparing and presenting financial statements for non-profit organizations, especially the HKBP Church, has encouraged the Indonesian Institute of Accountants (IAI) to develop a new interpretation of financial reporting standards, namely ISAK 35 Interpretation of Financial Accounting Standards Number 35 (ISAK 35) which is one of the revisions of PSAK 1 : Presentation of Financial Statements, to facilitate the preparation and presentation of financial statements that are easier to understand, relevant and comparable to internal and external parties. This standard will help and simplify HKBP Bolon in collecting external sources (sponsors). The purpose of this study is to understand the comparison of financial statements in HKBP Bolon with their financial statements sorted according to ISAK 35. This study uses a qualitative method. This study uses descriptive analysis method by comparing the theory contained in ISAK 35 with the practice contained in HKBP Bolon. The data collection technique in this research is observation. The results show that the financial statements of HKBP Bolon are only in the form of income and expenditure reports, so they are not in accordance with current standards, especially ISAK 35. The conclusion of this study is that HKBP Bolon has not designed its financial reporting process in accordance with current standards, especially ISAK 35.